Implementation of discourse analysis in aphasia: investigating the feasibility of a Knowledge-to-Action intervention. Issue 1 (2nd January 2019) - Bryant, Lucy; Ferguson, Alison; Valentine, Megan; Spencer, Elizabeth
ABSTRACT: Background : Linguistic discourse analysis is frequently used in aphasia research but is met with frequent calls for greater clinical application by speech pathologists and discussion of barriers and facilitators to clinical use. When examined in the clinical context, applications of linguistic discourse analysis were reportedly limited by knowledge and time-based barriers. Implementation science was used to guide the development of an intervention to overcome these barriers and bridge a Knowledge-to-Action gap. Aims : This study aimed to examine whether speech pathologists were able to translate knowledge and skills acquired during an implementation intervention to the assessment of a person with aphasia. The content of the intervention and the feasibility of the implementation strategy were also investigated. Transcription-based and transcription-less approaches to linguistic discourse analysis were compared. Methods & Procedures : Twenty-nine students in their final year of Australian speech pathology university degrees participated in a preliminary Knowledge-to-Action Intervention. Four intervention conditions targeted different evidence-based modes of discourse analysis: one transcription-less approach (judgement-based analysis) and three transcription-based approaches (manual, computer-assisted, and automated analysis). Participants completed evaluations at pre- and post-intervention and a six-month follow-up examining the knowledge acquisition, application, and implementation to practice. Outcomes were subject to content and statistical analysis to examine changes across time-points. Outcomes & Results : Following the intervention, participants set significantly more goals within contexts of discourse production and described significantly more discourse-based therapy approaches. Knowledge and skills acquired during the intervention were adapted by participants, with moderate maintenance observed at follow-up. Participants reported a lack of opportunity to implement their newly acquired skills to clinical practice. Conclusions & Implications : Specific training in the use of discourse analysis led to significant changes in assessment outcomes across all discourse analysis conditions. However, training alone did not remove the challenges involved in implementation. Participant feedback will help guide a more comprehensive intervention strategy with refined content to better facilitate the implementation of linguistic discourse analysis research in speech pathology practice.